SMEs Performance: Market Orientation, Entrepreneurship, and Dynamic Capabilities in Indonesia - Prasetyo, Johan Hendri; Winarti, Ch. Endah; Erasashanti, Annathasia Puji; Karunia, R. Luki; Rachman, Hikmah Abdul (Universitas Mercu Buana, 2024)
This research seeks to explore the influence of market orientation and entrepreneurship on the dynamic capabilities and performance of small and medium-sized enterprises (SMEs) in Indonesia. The focus of the study is specifically on culinary SMEs situated in the Jabodetabek Region, utilizing a quantitative-causal research methodology. The sample consists of 220 culinary SMEs with a business history exceeding 5 years, and data analysis was carried out using the PLS-SEM approach. The findings from the analysis of these 220 culinary SMEs reveal the potential of market orientation and entrepreneurship to enhance dynamic capabilities and SME performance. Moreover, the study highlights the positive impact of dynamic capabilities on SME performance and identifies an indirect pathway through which market orientation and entrepreneurship can amplify SME performance by utilizing the mediating role of dynamic capabilities.